2008
DOI: 10.1002/jnr.21696
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of neuronal differentiation through activation of N‐methyl‐D‐aspartate receptors transiently expressed by undifferentiated neural progenitor cells in fetal rat neocortex

Abstract: Neural progenitor cell is a generic term for undifferentiated cell populations composed of neural stem, neuronal progenitor, and glial progenitor cells with abilities for self-renewal and multipotentiality. In this study, we have attempted to evaluate the possible functional expression of N-methyl-D-aspartate (NMDA) receptors by neural progenitor cells prepared from neocortex of 18-day-old embryonic rats. Cells were cultured in the presence of basic fibroblast growth factor (bFGF) for different periods up to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 30 publications
1
14
1
Order By: Relevance
“…In the rat neocortical lower cell layer before culture, mRNA expression was seen for NR1, NR2A-2C, and NR2D subunits of the NMDAR subtype; GluR1 -4 subunits of the AMPAR subtype; and GluR5, GluR6, GluR7, KA1, and KA2 subunits of the KAR subtype on RT-PCR analysis (57). In neocortical neurospheres cultured for 12 days, mRNA expression was similarly seen for NR2A-2C subunits of NMDAR; GluR1 -4 subunits of AMPAR; and GluR5, GluR6, KA1, and KA2 subunits of KAR, but not for NR1 and NR2D subunits of NMDAR and the GluR7 subunit of KAR.…”
Section: Glutamatergic Machineriesmentioning
confidence: 99%
“…In the rat neocortical lower cell layer before culture, mRNA expression was seen for NR1, NR2A-2C, and NR2D subunits of the NMDAR subtype; GluR1 -4 subunits of the AMPAR subtype; and GluR5, GluR6, GluR7, KA1, and KA2 subunits of the KAR subtype on RT-PCR analysis (57). In neocortical neurospheres cultured for 12 days, mRNA expression was similarly seen for NR2A-2C subunits of NMDAR; GluR1 -4 subunits of AMPAR; and GluR5, GluR6, KA1, and KA2 subunits of KAR, but not for NR1 and NR2D subunits of NMDAR and the GluR7 subunit of KAR.…”
Section: Glutamatergic Machineriesmentioning
confidence: 99%
“…Evidence based on cultured NSCs supports the finding that nNOS gene expression is involved in the feedback modulation of NSC differentiation by NMDARs (Hu et al, 2008). Interestingly, several other studies using NSC cultures have suggested that NMDA activation could promote the neuronal fate determination of NSCs (Deisseroth et al, 2004;Kitayama et al, 2004;Yoneyama et al, 2008). Hence, the differentiation and proliferation of NSCs is likely subtly regulated by activity within a range; too-high or too-low levels of neuronal activity can both delay the process of neurogenesis.…”
Section: Factors Regulating Nsc Differentiationmentioning
confidence: 70%
“…extracellular glycine is effectively increased by blocking GLYT1 and that this mediates synaptic integration by dual activation of both the glycine receptor and the NMDA receptor [20,21]. Numerous previous studies have shown that proliferation of NPCs is regulated by activation of various receptors and these neurotransmitters; i.e., activation of the GABAA receptor, group I metabotropic glutamate (mGlu) receptor or dopamine D 3 receptor enhances proliferation of NPCs [22][23][24], whereas activation of the NMDA receptor, group III mGlu receptor, or α4β2 nicotinic acetylcholine receptor suppresses proliferative activity [25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%